Preoperative Enteral Nutrition and Surgical Outcomes in Adults with Crohn’s Disease: A Systematic Review - Anabela Rocha; Inês Bessa; Paula Lago; Marisa D. Santos; Júlio Leite; Fernando Castro-Poças (GE: Portuguese Journal of Gastroenterology, 2018)
Background and Aim: Enteral nutrition (EN) is applicable to adult Crohn’s disease (CD) in treating malnutrition and in inducing remission – here as a less effective alternative than corticosteroids. The purpose of this review is to determine whether preoperative EN impacts postoperative complications of adult CD, either by means of nutritional or therapeutic effects. Summary: A systematic review of English written full-text research articles published between January 1990 and November 2017, including adult patients undergoing abdominal surgery for complicated CD after EN, was performed. Four studies out of 22 were selected, all of which institutional, retrospective, case-control cohorts, one classified as “good quality” and three as “poor quality,” as rated by the Newcastle-Ottawa Scale. The application of inclusion and exclusion criteria resulted in a non-intentional absence of studies referring to supplemental EN among those reviewed. The reduced number of heterogeneous eligible studies impeded meta-analysis. In all studies, exclusive EN (EEN) was used and well tolerated, allowing to defer or even avoid surgery altogether, improving patients’ global state. The two studies with the greatest number of patients found preoperative EEN to be an independent factor against infectious and non-infectious complications in 219 patients and against anastomotic leaks or abscesses in 38 patients. Also, in univariate analysis, EEN was found to increase preoperative immunosuppressant-free intervals and to protect against anastomotic dehiscences, intra-abdominal abscesses, surgical wound infections, ileus, stomas, and reoperations in the largest study; in another study it was related to fewer intra-abdominal septic complications. Key Messages: All reviewed studies are retrospective and, consequently, of limited relevance. Nonetheless, all of them call the attention of the scientific community to the potential benefits of preoperative EEN on postoperative outcomes in adult CD, calling for prospective multi-institutional studies and randomized controlled trials.